MUSEUM NETWORKS AND SUSTAINABLE TOURISM MANAGEMENT. THE CASE STUDY OF MARCHE REGION’S MUSEUMS (ITALY) - Cerquetti, Mara; Montella, Marta Maria (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2015)
Over the past twenty years, research on cultural tourism has sought to find a balance between tourism development and cultural heritage conservation. However scholars have not focused on the enhancement of local cultural heritage as an asset to raise awareness of new cultural destinations and to prevent overcrowding in just a few cultural cities. After a discussion of literature on heritage tourism management, this paper presents the results of a survey on museum networks in the Marche Region of Italy. Research suggests that museum networks have an important role in promoting local cultural heritage, but that they are not yet able to exploit economies of scale, to then ensure the museums’ survival and development as well as their contribution to sustainable tourism.